Sustainable Strengthening of Concrete Using Lathe Waste Steel Fibers: Experimental and FEA Analysis: Sustainable Fiber Reinforced Concrete - Fawad Ahmad; Aiman Aiman Al-Odaini; Mohammad Nizamuddin Inamdar; Muhammad Majid Naeem; Muhammad Omair; Hamza Rafiq; Muaz Irfan (Advance Sustainable Science Engineering and Technology, 2025)
The construction industry is growing fast and increasing the demand for concrete which requires sustainable materials. Concrete is weak in tension and needs fiber reinforcement to improve strength. This study explores lathe waste steel fibers as a sustainable option to enhance tensile properties. Local industries produce large amounts of lathe waste that can be used in fiber-reinforced concrete. Traditional destructive testing is expensive and slow because it needs heavy machinery like Universal Testing Machines. This research combines destructive and computational analysis using ANSYS 15 for finite element modeling. Cylindrical and beam specimens were tested with fiber ratios from 0 to 3 percent. Results show that 2.5 percent fiber content gives the best compressive and flexural strength. Scanning electron microscopy confirms stronger bonding as fibers break within the matrix instead of pulling out. This study proves lathe waste steel fibers improve both performance and sustainability in construction